Analysis of the Impact of Controller Variation and Battery Efficiency on the Performance of Light Electric Vehicles - Fuad Abdillah (Journal of Mechanical Engineering, 2026)
Electric vehicles (EVs) have emerged as a sustainable transportation alternative to reduce fossil fuel dependence and carbon emissions. However, EV performance is strongly influenced by battery efficiency and control system configuration, particularly controller selection. This study analyzes how controller variation and battery efficiency affect the performance of the Viar EV1 1000W electric motor. An experimental approach compared Bosch and QS Motor controllers on a 1000W BLDC motor, with torque, power, speed, voltage, and battery efficiency systematically measured using a dynamometer and digital multimeter. Results demonstrate that the QS Motor controller significantly outperforms Bosch across all parameters delivering higher torque, power, speed, voltage stability, and battery efficiency. The study concludes that QS Motor controller implementation enhances performance and efficiency in light EVs such as the Viar EV1 1000W. This research contributes practical insights for the automotive industry on selecting optimal controllers to improve energy efficiency and system reliability in electric vehicles.